Makanlah seperti kamu Mengetahuinya: Bagaimana Makan yang Terkendali dan Jenis Kelamin memengaruhi Pilihan Makanan Sehat - Muhammad Maulana; Anna Undarwati (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2025)
Obesity will stay as a global health issue if individuals continue to engage in unhealthy eating behaviors and insufficient consumption of nutritious food. This study seeks to explore how gender and restrained eating style influence healthy food choices in Indonesia. This study uses a quasi-experimental design which includes self-reported measures through the DEBQ questionnaire, alongside a behavioral experiment conducted in a Dummy Supermarket, with 185 undergraduates’ students being participants. The findings indicate that two factors, gender (p = .015) and restrained eating style (p = .001), significantly impacted individuals’ healthy food choices. This is evidenced by the quantity of food items selected from the dummy supermarket, highlighting the meaningful role these factors play in healthy food selections. The interaction effect of gender and restrained eating style on healthy food choice was not significant (p = .074), indicating that the combined influence of these two factors did not produce a distinct effect beyond their individual contributions. These findings offer essential insight for creating effetive interventions designed to enhance awareness, reduce the consumption of unhealthy products among adults, and potentially lead to a descrease in obesity rates especially in Indonesia.